Nether world: crime and the police courts in Victorian London - Gray, Drew D. (Reaktion Books, 2024)
"Nether World presents a rich, often humorous glimpse into everyday life in Victorian London through a revealing account of nineteenth-century police courts. People of all classes brought complaints to this court about those who had hurt, abused, or stolen from them--drunks, pickpockets, wife-beaters, and fraudsters--who were each in their turn judged by magistrates wielding broad summary powers. Delving into underexamined court records and the pages of a fast-developing newspaper industry, Drew D. Gray offers a fresh description of a vibrant, ever-changing metropolis and considers ongoing issues such as poverty, homelessness, violence, substance abuse, prostitution, and--of course--crime."